Kualitas Akrual Dan Manajemen Aktivitas Riil Seasoned Equity Offering Perusahaan High Technology Di Asia Pasifik - Sumiyati Sumiyati; Jogiyanto Hartono (Global Financial Accounting Journal, 2017)
Seasoned Equity Offering is a public stock offering after the Initial Public Offering. This study aims to determine the effect of accrual quality and management of real activity toward market reaction and performance of companies employed Seasoned Equity Offering (SEO) in high-technology companies in Asia Pacific. Sample of this research is employed by using purposive sampling with this following criteria; high technology companies in Asia Pacific that offering SEO in 2001-2015 and sample data of company should be available on OSIRIS database. In ultimate, the total final sample is obtained from 40 companies spread in Australia, China, Indonesia, India, South Korea, Malaysia, New Zealand, Singapore and Taiwan. This research is a study of events (event study) using 5-year-window that is two years before SEO, current year of SEO and two years after SEO. The hypothesis is analyzed using Ordinary Least Square (OLS) for each events t-2, t-1, t0, t+1 dan t+2. The test results showed evidence that accrual quality had positive effects on performance of companies employed SEO. Yet, the results of second hypothesis testing, accrual quality measured by deviation standard, do not influence market reaction. This study can also prove management of real activity measured by abnormal cash flow. Abnormal can degrade the performance of SEO companies after the event, while the abnormal of cost discretioner does not influence performance. The fourth hypothesis testing results showed evidence that negative effect of SEO market reaction is definitely caused by pessimistic reaction of investor toward the performance of company employed SEO.